Konsep ‘Urf dalam Penetapan Hukum Islam - Sunan Autad Sarjana; Imam Kamaluddin Suratman (Universitas Darussalam Gontor, 2017)
An article discusses the concept of al-’urf which became one of the foundations of making Islamic law. This concept makes the law by taking something familiar in society, which have become their habit and were united with their lives, whether in the form of deeds or words. With note that when making Islamic law is surely without violating the basic teachings in Islam from the Qur’an and al-Sunnah. The application of al-‘urf leads to the acceptance of sharia by the community, without having to abandon the basic principles of Islam. The study of this concept is also the answer for contemporary Muslim thinkers who often encourage and insist to reform Islamic law through the mechanism of deconstruction and adapting to the principles of human rights. What they did is dangerous, because it changed the basic teaching in Islam, such as the obligation of fve times prayer, Ramadan fast, hajj, and so forth. In relation to al-’urf, these contemporary thinkers usually take up all the prevailing customs in society to make Islamic law, even these customs are contrary to the religious teachings. Through the study of the classical and contemporary books of jurisprudence, this article explains that Islamic teachings are appreciative and cooperative in addressing the growing cultural phenomenon in society. Islam still adopts and takes traditions that exist in society as one of the foundation of Islamic law, as long as those do not contrary to the teachings of Islam.